2020
DOI: 10.1021/acsami.0c11022
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Polymerization of Self-standing Covalent Organic Framework Films with High Performance in Molecular Separation

Abstract: Covalent organic frameworks (COFs) are typically isolated as microcrystalline powders. It remains fundamentally challenging to fabricate COFs into high-quality self-standing films to take full advantage of their ordered pore channels for molecular separation. Here, we report a new strategy for fabricating self-standing imine-linked COF films via homogeneous polymerization where films emerge from clear solutions without forming amorphous precipitates. The abundant basic nitrogen atoms of the monomers acted as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…Organic dyes reported to be rejected by COF-based nanofiltration membranes adsorb onto polycrystalline COF powders with high affinities, whereas dyes reported to pass through COF membranes do not adsorb strongly. For example, an unfunctionalized, imine-linked COF powder (TAPB-PDA, Scheme ) was introduced into separate aqueous solutions of six organic dyes (Scheme ) and mixed using an orbital shaker for 72 h. The dyes were selected because they were used in prior reports of COF membrane separations and span broad ranges of size, charge, and chemical structure. ,,, , The set of dyes included larger molecules that did not pass through the COF membranes (Rhodamine B [ RB ], Brilliant Blue G [ BB ]) , and smaller molecules that were passed by the membranes (4-nitrophenol [ NP ], 4-nitroaniline [ NA ]). ,, Despite being similar in size to those of the rejected dyes, Methylene Blue ( MB ) and Congo Red ( CR ) have demonstrated variable transport through different COF films and were also selected. ,,, , Visual inspection of the dye solutions after being in contact with the COF powder for 72 h indicated that the dyes adsorb to varying degrees (Figure S1): RB and BB adsorb strongly to the COF powder, leaving nearly colorless aqueous solutions above the solid COF. In contrast, almost no color change was observed for NP and NA -containing solutions under identical conditions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Organic dyes reported to be rejected by COF-based nanofiltration membranes adsorb onto polycrystalline COF powders with high affinities, whereas dyes reported to pass through COF membranes do not adsorb strongly. For example, an unfunctionalized, imine-linked COF powder (TAPB-PDA, Scheme ) was introduced into separate aqueous solutions of six organic dyes (Scheme ) and mixed using an orbital shaker for 72 h. The dyes were selected because they were used in prior reports of COF membrane separations and span broad ranges of size, charge, and chemical structure. ,,, , The set of dyes included larger molecules that did not pass through the COF membranes (Rhodamine B [ RB ], Brilliant Blue G [ BB ]) , and smaller molecules that were passed by the membranes (4-nitrophenol [ NP ], 4-nitroaniline [ NA ]). ,, Despite being similar in size to those of the rejected dyes, Methylene Blue ( MB ) and Congo Red ( CR ) have demonstrated variable transport through different COF films and were also selected. ,,, , Visual inspection of the dye solutions after being in contact with the COF powder for 72 h indicated that the dyes adsorb to varying degrees (Figure S1): RB and BB adsorb strongly to the COF powder, leaving nearly colorless aqueous solutions above the solid COF. In contrast, almost no color change was observed for NP and NA -containing solutions under identical conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Similar trends in capacity and affinity were also found for BND-TFB and BND-TFP COFs. To date, many so-called “membrane” experiments have been conducted by passing dilute dye solutions (≤100 mg L –1 ) through thick COF films. ,,, At these low concentrations, dyes with high association constants will almost completely adsorb to the COF, while those with low association constants will largely remain in solution, assuming that the COF is not near saturation. Given that polycrystalline COFs have uniformly high uptake capacities, and rejection performance is often characterized using small (<15 mL) volumes of dye solution, ,,, it is reasonable to expect that adsorption could play a dominant role in controlling the observed separation performance of these systems.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations